The Effectiveness of Tax Law Enforcement Against Tax Evasion Crimes in Indonesia - Nurlaila Sari; Khairul Nisa Lubis; Shintya Batu Bara; Nurleli Suseno; Nurhalim Perdana (ISNU Sumatera Utara, 2025)
Tax law enforcement in Indonesia is an important effort to reduce tax evasion practices that are detrimental to the state. Although Indonesia has adequate regulations, its effectiveness is still hampered by various factors, such as limited human resources at the Directorate General of Taxes (DGT), complexity of tax regulations, and low levels of taxpayer compliance. The growing use of information technology provides opportunities to improve transparency and effectiveness of supervision, but challenges related to implementation and lack of understanding by some taxpayers are still obstacles. This study aims to analyze the effectiveness of tax law enforcement in reducing tax evasion as well as the factors that support and hinder tax law enforcement in Indonesia. The results show that despite progress, further reforms are still needed in the tax system, strengthening the capacity of DGT human resources, and increasing public tax awareness to achieve a more effective and fair tax system.